On Integration of One Class of Systems of Lax-Type Equations - Lunyov, A.A.; Oliynyk, E.V. (Журнал математической физики, анализа, геометрии, 2015)
A nonlinear system of Lax-type equations is studied. The system is the basis of the construction of triangular models for commutative systems of linear non-selfadjoint bounded operators. Some of its solutions for n = 4 are described. In one of the cases, the general solution is explicitly expressed in terms of special (elliptic) functions.